2000
DOI: 10.1207/s15328023top2702_12
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Illustrating the Continuity of Behavior during Schedules of Reinforcement

Abstract: In this article, we present a method for illustrating the continuity of behavior during schedules of reinforcement. Students experienced either a fixed-interval 15-sec schedule in which the first contact after 15 sec of a cursor on a computer screen with a 0.7-cm diameter virtual (invisible) target resulted in reinforcement (a beep) or a fixed-ratio 5 schedule in which every 5th contact with the target produced the reinforcer. In addition to illustrating the continuity of behavior, this method provides a means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Research has shown that effective use of multimedia can increase student learning (Erwin & Rieppi, 1999;Fletcher-Flynn & Gravatt, 1995;Forsyth & Archer, 1997;Kazmerski & Blasko, 1999;McNeil & Nelson, 1991) and instructors are increasingly encouraged to incorporate multimedia into classroom teaching. Computerized demonstrations that are used for active learning exercises during class sessions and for supplementary, out-of-classroom learning and review have been developed for teaching: 1) introductory psychology (Chaparro & Halcomb, 1990;Worthington, Welsh, Archer, Mindes, & Forsyth, 1996), 2) research methods (Kazmerski & Blasko, 1999;Varnhagen & Digdon, 2002), 3) clinical diagnosis (Desrochers, House, & Seth, 2001;Jachna, Powsner, McIntyre, & Byck, 1993), 4) decision-making (Misale, Gillette, & del Mas, 1996), 5) perception and cognition (Neuhoff, 2000); 6) social psychology (Sherman, 1998), 7) behavioral principles (Lambert, 1987;Silva, Yuille, & Peters, 2000), and, most relevant for the current work, 8) statistics (Aberson, Berger, Healy, Kyle, & Romero, 2000;Britt, Sellinger, & Stillerman, 2002;Franklin & Cooley, 2002;Hurlburt, 2001;Richardson & Segal, 1998;Warner & Meehan, 2001;West & Ogden, 1998). Students consistently give favorable reviews to these computerbased learning resources emphasizing their interactive nature, ease of use, graphical presentation of material, and the ability to review concepts.…”
mentioning
confidence: 99%
“…Research has shown that effective use of multimedia can increase student learning (Erwin & Rieppi, 1999;Fletcher-Flynn & Gravatt, 1995;Forsyth & Archer, 1997;Kazmerski & Blasko, 1999;McNeil & Nelson, 1991) and instructors are increasingly encouraged to incorporate multimedia into classroom teaching. Computerized demonstrations that are used for active learning exercises during class sessions and for supplementary, out-of-classroom learning and review have been developed for teaching: 1) introductory psychology (Chaparro & Halcomb, 1990;Worthington, Welsh, Archer, Mindes, & Forsyth, 1996), 2) research methods (Kazmerski & Blasko, 1999;Varnhagen & Digdon, 2002), 3) clinical diagnosis (Desrochers, House, & Seth, 2001;Jachna, Powsner, McIntyre, & Byck, 1993), 4) decision-making (Misale, Gillette, & del Mas, 1996), 5) perception and cognition (Neuhoff, 2000); 6) social psychology (Sherman, 1998), 7) behavioral principles (Lambert, 1987;Silva, Yuille, & Peters, 2000), and, most relevant for the current work, 8) statistics (Aberson, Berger, Healy, Kyle, & Romero, 2000;Britt, Sellinger, & Stillerman, 2002;Franklin & Cooley, 2002;Hurlburt, 2001;Richardson & Segal, 1998;Warner & Meehan, 2001;West & Ogden, 1998). Students consistently give favorable reviews to these computerbased learning resources emphasizing their interactive nature, ease of use, graphical presentation of material, and the ability to review concepts.…”
mentioning
confidence: 99%
“…Silva (1999) introduced software for the Macintosh® operating system that allows students to study shaping. The software tracks how a student moves a cursor on a computer screen and shapes movements as a function of various parameters until the cursor "hits" a target (Silva, 1999;Silva, Yuille, & Peters, 2000).…”
mentioning
confidence: 99%